Exploring the Correlation between Glucose and Apoptosis Levels in Stored Platelets - Mohammad, Kaboli; Hadi, Bazzazi; Mohammad, Taher Hojjati; Shabnam, Tabasi; Khodaberdi, Kalavi; Fatemeh, Mohammadi; Seyed, Mojtaba Hoseiniharouni; Omolbanin, Majidian; Fresteh, Qazzaq (International Journal of Blood Transfusion, 2025)
Background and Objectives Platelets are small, anucleate blood cells produced in the bone marrow, primarily involved in blood coagulation. Platelet concentrate is a vital blood product with extensive applications. However, its short lifespan and limited donor availability pose global challenges. This study aimed to follow the trend of platelets 5 during days of storage. Material and Methods We studied on 40 platelet bags and analyzed glucose levels, lactate dehydrogenase (LDH), bacterial culture, and apoptosis using flow cytometry with Annexin V-PI over three consecutive days (first, third, and fifth) post-blood collection. Data were analyzed using SPSS. Results No significant correlations were found between age, blood group, or gender and the variables studied. No bacterial growth was detected. Glucose levels decreased significantly from day 1 (382 mg/dl) to day 5 (298 mg/dl). The average platelet apoptosis increased significantly from 3.65% on day 1 to 9.06% on day 5. Significant correlations were observed between glucose levels and apoptosis on days 3 (p<0.05) and 5 (p<0.01). No correlation found between LDH and apoptosis or necrosis, although a significant relationship between necrosis and apoptosis was noted on day 5 (p=0.003). Conclusion These findings suggest that while demographic factors do not influence the studied variables, the significant decrease in glucose levels correlates with increased platelet apoptosis over time, highlighting potential metabolic interactions that warrant further investigation.   Highlights 1. The study revealed subtle variations in metabolic markers related to donor demographics, particularly gender and age. Understanding these differences can inform targeted donor selection strategies to optimize platelet quality. 2. A significant negative correlation was found between glucose levels and apoptosis rates, indicating that as glucose decreases, platelet viability declines. This relationship highlights the need for careful monitoring of glucose levels during storage to maintain platelet function. 3. Fluctuations in lactate dehydrogenase (LDH) levels were correlated with increasing rates of apoptosis, suggesting that LDH could serve as a valuable biomarker for assessing platelet quality throughout the storage period. This finding could lead to improved storage protocols and enhanced transfusion safety.
Keywords: Apoptosis; Necrosis; Platelet Concentrate